Staphylococcus aureus Enterotoxin as a Major Risk Factor for Multiple Sclerosis Severity - Suhaib Khalid Ibrahim (Journal of Global Pharma Technology, 2019)
Background: Staphylococcus aureus produce enterotoxins that function as super antigens which activate auto reactive CD4+ T-cells potentially target the basic myelin protein into the CNS. Objective: This study investigates the correlation between the colonization of S. aureus harbouring enterotoxins with multiple sclerosis (MS) exacerbation. Methods: A total of 200 nasal swabs were collected from three study groups: Healthy controls as a Non-MS Subjects (n=100), relapsing remitting MS or exacerbated (n=50) and newly diagnosed MS. (n=50). S. aureus was isolated from the anterior nares of these groups following standard operating procedures. Antibiotic susceptibility test against 19 antibiotics using disk diffusion method were done. Staphylococcal super Antigen SeA, seB, seC genes were amplified using standard conventional polymerase chain reaction (PCR) technique and resolved by agarose gel electrophoresis. Results: In this study, Out of 100 MS patients and 100 healthy control groups, there were 36% and 46% males and 64% and 54% females respectively. A total of 81(81%) were colonized with S. aureus includes, 31(38.2%) newly diagnosed MS and 50(61.8%) exacerbated MS while only 12(12%) isolated from control non-MS group. All S. aureus isolates were resistant to Methicillin (100%) and sensitive to Impenem (100%). PCR results showed that, the frequency of enterotoxins (sea, seb and sec) in MS patients was (42.4%) including (40.8%) were from newly diagnosed and (43.3%) were from relapsing remitting while there is no enterotoxins was detected in control group. the prevalence of se A was significantly higher (p<0.00) in the MS exacerbation (72%) than in newly diagnosed group (64.5%). Conclusions: The frequency of S.aureus isolates and its enterotoxin seA gene is high in the MS patients and this gene serve as an important marker in the severity of MS disease. Also S.aureus isolates were sensitive to imipenem which is considered as a better choice for nasal decolonization of S.aureus in the MS patients. Keywords: Multiple sclerosis (MS), Staphylococcus aureus, Super antigens, Enterotoxin A, B, C.